2016
DOI: 10.1097/pcc.0000000000000864
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Sedation and Analgesia Practice Among Canadian Pediatric Critical Care Physicians*

Abstract: Our survey demonstrates great variation in practice in the management of pain and anxiety in Canadian PICUs. Standardized strategies for sedation, delirium and withdrawal, and sleep promotion are lacking. There is a need for research in this field and the development of evidence-based, pediatric sedation and analgesia guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…The latest clinical practice guidelines on analgesia and sedation for critically ill children was published in 2006 . Some surveys demonstrated a large diversity in pain and agitation management in PICUs, even in the same country . A survey in Japanese PICUs was performed in 2012 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latest clinical practice guidelines on analgesia and sedation for critically ill children was published in 2006 . Some surveys demonstrated a large diversity in pain and agitation management in PICUs, even in the same country . A survey in Japanese PICUs was performed in 2012 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous survey in 2012 reported that four out of 17 (24%) PICUs in Japan used sedation scales . In contrast, Canadian pediatric critical care physician‐based studies in 2015 reported that 84% of respondents used pain and sedation scales . Another international, physician‐based survey in 2012 reported that 70% of respondents used sedation scales .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With all the recent interest and research related to dexmedetomidine, it is becoming more and more common in the ICU. Dexmedetomidine has become a frequent choice for second- or third-line therapy and use is increasing [ 3 ]. The most commonly stated reason for not using dexmedetomidine is its cost, but the decrease in length of stay and dose required may start to mitigate the difference in cost.…”
Section: Reviewmentioning
confidence: 99%
“…Appropriate sedation and use of sedative medications is extremely important in pediatric burn patient due to the pain, anxiety, fear of strangers, separation from parents, and loss of control that can accompany burn injury [ 1 3 ]. Additional anxiety related to hospitalization, social situation, and long-term body image compound the problem [ 4 ].…”
Section: Introductionmentioning
confidence: 99%